Update on Nutritional Aspects of Gluten-Free Diet in Celiac Patients - Moreno, María de Lourdes; Comino, Isabel; Sousa, Carolina (Journal of Nutrients, 2014)
A strict gluten-free diet is the only currently available therapeutic treatment for patients with celiac disease, an autoimmune disorder of the small intestine associated with a permanent intolerance to gluten proteins. In recent years, the dramatically prompted changes in the dietary habit of an increasingly large population (celiac disease, non-celiac gluten sensitivity and gluten allergy) has resulted in rising demands for gluten-free products. Before starting gluten-free diet, alteration in intestinal absorption capacity of celiac patients involves deficiencies of nutrients, vitamins and dietary minerals. The habitual poor gluten-free food choices in addition to inherent deficiencies in the gluten-free diet of diagnosed celiac patients may relate with dietary inadequacies. Therefore dietary assessment and counseling at the time of celiac disease diagnosis and ongoing care are crucial as well as fortification of gluten-free foods also need to be considered. This article reviews the nutritional aspects of gluten-free diet in celiac patients and provides an up-date of dietetic recommendations to correct these deficiencies and to ensure optimum gluten-free diet compliance.